Validity of Kvisoft Flipbook Maker-Assisted PjBL-Based E-books for Elementary Schools - Feby Kharisna; Risda Amini (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The presence of Buku Sekolah Elektronik (BSE), an electronic textbook developed by the Ministry of Culture and Education, is one example of the application of TI in education. Observation and the requirements of instructors and students. The purpose of this research is to make and know the validity of a Project Based Learning-based e-book featured by a kvisoft flipbook maker in the third grade of elementary school. This research was conducted using Research and Development (RD) method and Model Pengembangan ADDIE. Researchers observed and interviewed teachers and third-grade students from each school as many as 3 people were selected for research. By using the data from observation and interviews, the researcher designed the product to fulfill the needs of those schools. In the 'development' session, the researcher developed the raw product so that it could be used by the teacher and students. During the